Análise tafonômica, paleoecológica e contextualização paleoambiental das concentrações fossilíferas dos arenitos Taió, SC - Schmidt Neto, Hugo (Universidade do Vale do Rio dos Sinos, 2013)
At the Taio city, Santa Catarina State, the Paraguassu Member presents a significant marine invertebrate fauna contained in layers of very fine sand, informally designed Layers Taio. Its congregation has developed into a post-glacial conditions was influenced by the melting of the final Itararé Group. Thus, the present study aimed to conduct paleoecological analysis of these deposits in order to elucidate the impact of the inflow of water from melting sea Taio. Therefore, went make a taphonomic study of repositories of scientific institutions of Rio Grande do Sul, Santa Catarina and São Paulo states, as the fossil record in outcrops (in situ). The profiles of sedimentary successions, fossiliferous areas were correlated from the comparison of their facies. The taphonomic signatures show little signs of rapid transportation and burial, with little colonization by organisms of bioclasts sponges. The pattern of occurrence of biofabric Rosselia isp. indicates the action of storm events and high-frequency sediment. A larger quantity of plant debris on the basis of the sequence indicates closer proximity to the coast, while forms tiny molluscs and echinoderms, suggesting facies that occur in a zone of shoreface indicate low water temperatures. The data obtained in this work indicate that the waters of the melting of the end of the Carboniferous continued impacting the marine fauna of the Sea Paraguaçu by floating its salinity and his conditioning at low temperatures.
Keywords: Mar Paraguaçu; Invertebrados; Paleoecologia; Tafonômia; Paraguaçu sea; Invertebrate; Palaeoecology; Taphonomy; ACCNPQ::Ciências Exatas e da Terra::Geologia